Palestinian activist says home raided ‘in revenge’ for appearing in Louis Theroux documentary - Pearce, Matthew (The Guardian, 2025)
Issa Amro shares videos of confrontations with balaclava-clad military who he claims ‘want revenge’ after the BBC film The Settlers
Israel
Keywords: Culture; Israel; Israel-Gaza war; Louis Theroux; Social media; Television; Television & radio